Ergo-Physiology Decreases Work Postur Risk and LBP in Red Land Workers in Bosen Village, North Mollo Sub-District, South Central Timor District - Jacob M Ratu (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
The work of digging red earth is one of the physical activities of lifting and carrying. The field conditions of work, the slope level of the land wall and work aids used are one of the reasons why workers work with a bent and twisted posture. Such an posture increases the risk of Low Back Pain (LBP). LBP can reduce work capacity and productivity and in the long time reduce the quality of health and life of workers. For this reason, ergo-physiological intervention is carried out with the aim of reducing the level of risk of work posture and LBP. This research is an experimental study using the same subject design involving 30 red earth digg workers in Bosen Village as the subject of the research. Ergo-physiological interventions are given in the form of improving work posture and physiotherapy training. Improvement of work posture is focused on activities, digging move, and carrying excavated material and lifting excavated material onto transport trucks. Physiotherapy training uses a modified William flexion exercise method. Measuring the level of risk of the work posture using the REBA method and the LBP level using the modified LBP Oswestry questionnaire, carried out before and after the intervention. Differences in data before and after the intervention were tested using different tests of paired t test for normal distributed data and Wilcoxon Sign Rank test for data that were not normally distributed, each using a significance level of 5%. The results showed a decrease in the risk level of work posture and LBP of red earth digger workers is of 3.37 (34.56%) and 1.24 (32.29%) respectively. It was concluded that ergo-physiological interventions effectively reduce the risk of work posture and the level of LBP of red earth digger workers.